The Neutral Sphingomyelinase 2 Is Required to Polarize and Sustain T Cell Receptor Signaling - Börtlein, Charlene; Draeger, Annette; Schoenauer, Roman; Kuhlemann, Alexander; Sauer, Markus; Schneider-Schaulies, Sibylle; Avota, Elita (Frontiers in Immunology, 2018)
By promoting ceramide release at the cytosolic membrane leaflet, the neutral sphingomyelinase 2 (NSM) is capable of organizing receptor and signalosome segregation. Its role in T cell receptor (TCR) signaling remained so far unknown. We now show that TCR-driven NSM activation is dispensable for TCR clustering and initial phosphorylation, but of crucial importance for further signal amplification. In particular, at low doses of TCR stimulatory antibodies, NSM is required for Ca2+ mobilization and T cell proliferation. NSM deficient T cells lack sustained CD3ζ and ZAP-70 phosphorylation and are unable to polarize and stabilize their microtubular system. We identified PKCζ as the key NSM downstream effector in this second wave of TCR signaling supporting dynamics of microtubule-organizing center (MTOC). Ceramide supplementation rescued PKCζ membrane recruitment and MTOC translocation in NSM deficient cells. These findings identify the NSM as essential in TCR signaling when dynamic cytoskeletal reorganization promotes continued lateral and vertical supply of TCR signaling components: CD3ζ, Zap70 and PKCζ, and functional immune synapses (IS) are organized and stabilized via MTOC polarization.